A narrative exploration of psilocybin’s potential in mental health - Min, Huitae; Soon Young Park; Park, Jisu; Na, Seongsu; Lee, Hoe-Suk; Kim, Taejung; Ham, Jungyeob; Park, Young Tae (Frontiers Media S.A., 2024)
Psilocybin, a psychoactive substance, has recently garnered attention for its high therapeutic potential in psychiatry. In this study, we investigated the multifaceted aspects of psilocybin, highlighting its chemical properties, mechanisms of action, and burgeoning role in psychiatric treatment. Furthermore, we examined the clinical applications and potential therapeutic benefits of psilocybin in the treatment of various mental health disorders, supported by accumulating clinical evidence. This review aims to deepen our understanding of the clinical impact of psilocybin, elucidate its therapeutic value, and propose directions for future research, thereby paving the way for its integration into mainstream psychiatric treatments. Psilocybin has been shown to be safe in clinical trials with manageable side effects. However, additional safety measures are required after this discussion, including dosing protocols, patient monitoring, and distress management strategies.